A novel strategy to determine the 1-repetition maximum in the jump squat exercise - Loturco, I.; McGuigan, M. R.; Rodríguez-Rosell, D.; Pereira, L. A.; Pareja-Blanco, F. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to determine the maximum relative load of the half-squat (HS; i.e., % HS 1-repetition maximum [1RM]) that can be used in its ballistic variation, namely, the jump squat (JS) exercise, and to examine whether this reference value varies in subjects with different strength levels. In total, 186 elite athletes from 10 distinct sport disciplines participated in this study. A progressive loading test up to HS 1RM was performed during the competitive phase of the season for all athletes. Mean propulsive velocity and propulsive phase duration were also assessed during the 1RM test. Athletes were divided into 3 distinct subgroups: "low," "middle," and "high" strength levels, based on their relative HS 1RM values (kg·kg-1). A 1-way analysis of variance was used to compare the variables assessed between the groups. Significance level was set at p < 0.05. The high group demonstrated the highest relative HS 1RM values, followed by the middle and low groups (all p < 0.05). No significant differences were observed between the groups for the remaining variables (p > 0.05). It was observed that at 86.0 ± 5.4% 1RM, the full concentric action can already be considered as entirely propulsive in the HS exercise for all subjects, independent of their strength levels. Therefore, this relative strength value may be used as a reference for the 1RM in the JS exercise.